Testing dynamic component of strength ability in 10-17 year-old footballers - Zlygostev, O. V. (Theory and Practice of Physical Culture, 2017)
The modern football sport reserve training systems give a high priority to strength tests to assess the player`s ability to effectively play and compete in matches. Objective of the study was to complete a set of system tests to obtain the strength ability variation data and apply them for further improvement of the 10-17 year-old footballers` training stages within an annual training cycle. The study was designed to analyse the strength ability variation data obtained by isometric dynamometry of the knee and hip extension movement. The dynamometric test data showed that the period between the ages of 12 and 14 years is the most sensitive to the strength- and speed-strength training and reasonable strength and speed-strength building tools should be applied on a differentiated basis in this period to secure success of the relevant abilities development process.